The Replacement of Criminal Fine in Criminal Taxation - Putri Ayu Wulandari; Mochammad Zaidun (Universitas Airlangga, 2019)
The absence of provisions regulating the substitution of criminal fines in the KUP Law, raises legal uncertainty for law enforcement officials, especially prosecutors in executing court decisions. Considering the recovery of state financial losses that can be resolved by the consistency of court decisions, so the provisions in the KUP Law must meet the legal principles in criminal fines in criminal taxation acts. By not clearly stipulated the substitution of criminal fines in the KUP Law raises legal uncertainty. While substituting criminal fines in the KUP Law is only in the form of imprisonment. In practice, there are several forms of court rulings, there are substituting criminal fines with imprisonment, substituting criminal fines with confiscation of assets then auctioned to pay underpayment taxes, substituting criminal fines with confiscation of assets then auctioned to pay underpayment taxes if the convicted person does not have property that is adequate then replaced with imprisonment. The formulation of the legal issues in this study are: (1) the philosophy of substituting criminal fines in criminal acts in the taxation field, (2) Characteristics of substitution of criminal fines in criminal acts in the taxation field. The results of this study are expected to have a conceptual and legal reforms related to substituting criminal fines in criminal acts in the taxation field, so as to ensure legal certainty, justice and benefit, then the replacement of criminal substitute fines in criminal acts in the taxation field must be included in court decisions and followed up with execution of court decision by the Prosecutor as the executor.